A atuação das dimensões recursos e agência nas redes estratégicas como vetor para o empoderamento e empreendedorismo feminino - Almeida, Liliane Matias de (2022)
Problems such as the wage gap between men and women, limited access due to motherhood, among other sensitive issues, have been a reason for struggle on the part of women in Brazil and around the world. In this context, in search of alternatives, female entrepreneurship has grown and demonstrated its importance for the economic development of communities and nations. Similarly, women have seen entrepreneurship as an opportunity for growth and overcoming barriers, both as a strategy for women's empowerment and for achieving financial independence, however the entrepreneurial context of developing economies such as Brazil presents numerous challenges for the female entrepreneurship, both due to gender barriers and the lack of public policies. In this way, women seek in female entrepreneurship a solution to earn a living, and strategic networks are presented as an important catalyst in this situation, empowering women entrepreneurs or to undertake. This study sought to investigate two dimensions, resources and agency, the first being related to external factors that are the tools and opportunities available for access, and the second internal factors that is understood as autonomy and personal development for decision making. The resource and agency dimensions are considered two strategic processes of female empowerment, in light of the performance of strategic support networks and their impact on female entrepreneurship in Brazil, resulting in the structural equation “the performance of the resource and agency dimensions in strategic networks as a vector for female empowerment and entrepreneurship” to conduct the investigation. The mixed methodology was adopted, starting with a qualitative study through semi-structured interviews with 11 women representatives of strategic networks focused on the development of women, which generated 12 hours and 35 minutes of recording and 255 pages of transcription. The quantitative study was carried out through the application of a survey with 354 women entrepreneurs in the context of six Brazilian cities. Qualitative results indicate the importance of strategic networks as essential elements to foster female empowerment, as well as to take even greater advantage of the number of opportunities for women entrepreneurs, in addition to identifying the use of resource and agency dimensions as tools to plan and offer services. with a focus on women's development. It is evident that women, as they have less access to resources such as knowledge and microcredit, leverage the agency's non-action, that is, they have less self-confidence and autonomy, which makes it difficult to see personal and professional goals. The quantitative results, with the hypothesis test, made it possible to validate the proposed conceptual model, demonstrating that the dimensions agency and resources have a positive and significant effect on female empowerment, however, the effect of agency, that is, the internal factors, is stronger than the effect of resources. This thesis innovates by proposing a conceptual model applied to assess the impact of the resource and agency dimensions of female empowerment on female entrepreneurship, considering the role of strategic support networks for female entrepreneurs. The managerial contribution consists of using the model to measure a woman's level of empowerment, and working individually on deficiencies to develop her efficiently to achieve assertive results. It is also known that the main reason to undertake is because of not finding space in the labor market, including reasons such as motherhood and the search for financial independence, and it is expected that the results of the thesis, given the reality of the challenges imposed by society , indicate ways for women to gain space, voice and opportunities in entrepreneurship. Also understanding that the agency dimension (internal factors) has more power than the resources (external factors) achieving more robust results, strategic networks can improve performance by anticipating the tools for personal development, improving the chances of the dimension acting resources. It is also important to highlight that the results can collaborate with a more vigorous work in the direction of black women from less favored regions, contributing with strategic networks focused on these regions.